Managing forest ecosystem services for hydropower production. Issue 61 (July 2016) - Vogl, Adrian L.; Dennedy-Frank, P. James; Wolny, Stacie; Johnson, Justin A.; Hamel, Perrine; Narain, Urvashi; Vaidya, Anil
Highlights: Targeting watershed management for hydropower benefits can improve sediment retention. Interventions protect & restore forests, provide alternatives for fuel and fodder. Management interventions are shown to decrease sediment delivery by up to 44%. While sediment delivery decreases, annual water yield also declines slightly (<1%). Modeling ecosystem services in a participatory process increases policy relevance. Abstract: In many countries, hydropower development is rapidly becoming a focus of green growth policies. This represents a significant opportunity for ecosystem services-based land management that integrates environmental and development goals to benefit the hydropower sector and support economic growth. In this study, we present an approach for targeting ecosystem-provision investment in hydropower catchments coupled with hydrologic modeling to quantify the benefits of soil and water conservation activities. We demonstrate the application of this approach in five hydropower facility catchments in the state of Himachal Pradesh, India. The results show that there is a high potential for targeted soil and water conservation to increase sediment retention services that benefit hydropower facilities (up to a 44% reduction in sediment transported from uplands into streams), although this benefit is distributed non-uniformly across catchments and levels of investment. The extent to which services can be improved is strongly driven by current land use and management practices that impact how and where conservation activities can be located. Iterative use of the method described here, in a process of stakeholder engagement and capacity-building, enables policy makers to determine the optimal mix of land management strategies and budget allocation to maximize service improvements that support hydropower production.